BINGKAI BERITA PENGGALANGAN BANTUAN KEMANUSIAAN UNTUK RAKYAT PALESTINA DI MEDIA ONLINE REPUBLIKA.CO.ID DAN KOMPAS.COM - Kurniansyah, Rafli Akram; Toni, Ahmad; Siregar, Rachmi Kurnia (Universitas Muhammadiyah Jakarta, 2024)
The 'heating' conflict in the Gaza Strip which triggered a war between Palestine and Israeli Zionists from October 2023 until now continues to raise concern worldwide, including Indonesia. This concern was realized by sending various aid to Palestine. This humanitarian action was widely reported by various mass media, including online media republika.co.id and kompas.com. The news selection was chosen from 13 October – 4 November 2023 with certain considerations. This research uses a qualitative descriptive approach with a constructivist paradigm. Researchers framed news about raising humanitarian aid for the Palestinian people on republika.co.id and kompas.com using Robert N Entman's framing analysis approach. In the period 13 October – 4 November 2023, Republika.co.id broadcast 13 news stories while Kompas.com released 10 news stories. The results of this research show that there are similarities between the two news portals, namely that they both raise the issue of raising humanitarian aid to help the Palestinian people as part of the overall media coverage. The difference is that Republika.co.id emphasizes the movement of elements of society in mobilizing humanitarian action as